Peran Strategis dan Upaya Kepolisian Dalam Menanggulangi Serta Menangkal Tindak Pidana Curanmor di Wilayah Hukum Polres Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Febri Anugrah Pertama; Agus Ariadi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
Economic growth and accelerated regional development in Ogan Ilir Regency have contributed to a significant rise in motor vehicle ownership, which has simultaneously driven an escalation of motor vehicle theft (curanmor). This phenomenon causes material losses for victims and generates pervasive insecurity within the community. This study aims to analyze the strategic role of the Ogan Ilir Resort Police in combating motor vehicle theft, identify the underlying causes and operational obstacles encountered, and formulate concrete measures to enhance crime control effectiveness. A descriptive qualitative approach was employed through library research. Data were gathered from statutory regulations, legal texts, and relevant scientific sources, and analyzed systematically using content analysis techniques. Findings reveal that the Ogan Ilir Resort Police has implemented three primary functions: prevention (preventif), law enforcement (represif), and community guidance (preemtif). However, overall effectiveness remains suboptimal due to insufficient infrastructure, evolving perpetrator methods, and low levels of active community participation in environmental surveillance. Effective suppression of motor vehicle theft requires integrated synergy among the police, the community, and local government. Cross-sector collaboration is identified as a fundamental prerequisite for achieving a safe and law-abiding environment in Ogan Ilir Regency.